Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Tempe Kedelai Cap Samudra pada Konsumen di Pasar Tawangsari Sukoharjo - Setiawan, Rifky; Sumaryanto (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Cap Samudra soya tempeh is one of the growing tempeh brands that prioritises safe and halal products. Although as the business world develops, more and more products are offered in the market. This also makes the consumer mindset more developed in choosing products by paying attention to factors such as price, product quality, and promotion. These factors will lead to consumer purchasing decisions. This study aims to analyse the significance of price, product quality, and price on purchasing decisions for soybean tempeh cap samudra for consumers in the Tawangsari Sukoharjo Market. The population of this study were consumers of soybean tempeh cap samudra. The type of data used in this study is quantitative data. The data source used is primary data. The sample in this study were 100 people. The method used in sampling is purposive sampling using certain criteria. The data collection technique in this study used a questionnaire. The classic assumption test uses tests: multicollinearity, autocorrelation, heteroscedasticity, and normality. Data analysis techniques using multiple linear regression tests, t tests, F tests, and R2 tests. The results show that price (X1), product quality (X2), promotion (X3) have a significant effect on purchasing decisions for consumers of oceanic cap soybean tempeh.